Sterner Response toward Rape in line with Islamic Law: Special Reference to Pakistan - Shahid, Shahzeb (Faculty of Law, Universitas Negeri Semarang, 2021)
This paper tends to examine the nature of rape crime under Islamic law in order to take sterner action against this crime in line with Islamic law. As the Holy Quran does not directly deal with rape crime, for this reason, there is a wide range of disagreement among jurists regarding the issue of rape crime. Rape is not a single dimension issue, therefore, this paper is meant to shed light on issues related to rape such as whether or not rape is a separate crime? When does sexual intercourse amount to rape? What does Islam prescribe punishment for a person who is coerced to commit rape? Does Islam permit abortion for raped women? Why marital rape does not exist in Islam? Whether rapists may be awarded the punishment of lashes, Imprisonment or death as tÃ¢â‚¬Ëœazir or syasah? This paper finds out what Zina (fornication) is under Islamic law because in Islamic jurisprudence only coerced Zina is regarded as rape. Thus, this paper is classifying rape in the same category as Zina. By classifying rape as a subset of Zina can only sort out the juridical issues that are emanating from coerced Zina. However, Some modern scholars put rape in a category of Hirabbah crime in order to circumvent the strict evidentiary procedure of Zina(fornication) crime. This paper depicts that there is no need to put rape in the domain of Hirabah because Islamic law permits the ruler or legislation to award punishment of lashes or death as Tazir or Syasah without waiting for the four pious Muslim male eye witness and inflicting Hadd of Qadaf(slander) to the complainant. Finally, this paper is exploring the options that may be taken in order to nip this crime in the bud.